IMPLEMENTASI KEBIJAKAN PEMERINTAH TENTANG INFRASTRUKTUR KETENAGALISTRIKAN DI KOTA BANDUNG - Adibowo, Rino; Sidik Al Amin, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2025)
The purpose of this research is to find out the implementation of electricity policy in Bandung City. Implementation translates concepts into real actions that have an impact on everyday life. The theory used in this research is the theory of policy implementation according to George C. Edwards III (1980). There are four factors that determine the success of policy implementation, namely: communication, resources, disposition, bureaucratic structure. The method used in this research is a descriptive method with a qualitative approach. The data collection techniques used are literature study, observation, interviews and documentation. The technique of determining informants using purposive techniques to the Bandung City Transportation Agency Apparatus. The result of this research shows that the implementation of policy related to energy and electricity, in the form of community response study to electricity infrastructure, has not reached an optimal level. The research identifies a number of challenges in the implementation of the policy. Factors identified include communication constraints, including lack of education and gaps in access to technology, resource aspects, including theft of PJU components and complaints of outages despite a large budget, disposition, including lack of incentives for officials and communities who report, and bureaucratic structure, including weaknesses in reporting SOPs and lack of education from the Transportation Agency.